Effectiveness of reading aloud strategies on low proficiency Pakistani college level female students of English department from humanities group at higher secondary system: A teachers’ perception - Mehmood Sajid, Muhammad Khalid; Hafizoah, Kassim; Al Fraidan, Abdullah; Adnan Hasan, Ghassan; Iqbal, Zafar; Aljarrah, Khaled; Al Anazi, Nawaf (Information Technology in Industry, 2021)
Reading is an important part of learning. No one can deny its importance. The importance of reading aloud strategies has increased. Reading aloud strategies are very important, especially for low proficiency students and for those who use the English language as a second language. It is vital for low proficiency students at the national and international levels. This study examines the effectiveness of the read-aloud strategies on low proficiency students at the secondary school level in Multan city. The study was conducted at the higher secondary school of Multan city in Pakistan; data were collected from students of the first year through a questionnaire, and pre-test post-test instruments were also used. The study is based on an experimental research design, and the target sample was 20 students of humanities group and five teachers from the English department. The study found that the reading aloud strategies help low proficiency students at the college level in Pakistan.